Respostas
respondido por:
2
Olá Adriana
-3(3x - 42) = 2(7x - 52)
-9x + 126 = 14x - 104
- 9x - 14x = - 104 - 126
- 23x = - 230 ( -1)
23x = 230
x = 230/23
x = 10
Bons estudos.
adrianamoura31:
obrigada
respondido por:
1
-3(3x-42) = 2(7x-52)
-9x + 126 = 14x - 104
-9x - 14x = - 104 - 126
- 23x = - 230 (-1)
23x= 230
x = 230/23
X = 10
-9x + 126 = 14x - 104
-9x - 14x = - 104 - 126
- 23x = - 230 (-1)
23x= 230
x = 230/23
X = 10
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás